Patterns of parasite distribution in the hybrids of non-congeneric cyprinid fish species: is asymmetry in parasite infection the result of limited coadaptation? - Krasnovyd, Vadym; Vetešník, Lukáš; Gettová, Lenka; Civáňová, Kristína; Šimková, Andrea (International journal for parasitology, 2017)
Hybrids and their parasite diversity represent interesting models for evolutionary ecology. The modified immune response, shifted ecology, inheritance, and maternal ancestry of hybrid host fish are supposed to affect the diversity of their parasite communities. The pattern of metazoan parasite distribution in non-congeneric cyprinids - common bream (Abramis brama) and roach (Rutilus rutilus) (species with different morphology and ecology, and harbouring different specific parasites) - and their hybrids was analysed. Four static alternative scenarios based on parasite infection levels in hybrids and parental taxa are known. The hybrid resistance scenario predicts that hybrids are more resistant than parental taxa, resulting in low parasite infection in hybrids. This scenario is principally consistent with hybrid heterosis advantage. In accordance with this prediction, metazoan parasite abundance and prevalence were higher in parental species when compared with their hybrids. Alternatively, the dynamic Red Queen scenario of infection in hybridising systems predicts parasite adaptation to common hosts. Temporal (six sampling events) and spatial (two sampling sites) aspects as possible factors influencing parasite distribution were analysed. We found no support for this hypothesis, i.e. no changes in the frequency of hybrids or their parental species and no changes in parasite infection in parental species or hybrids were found in the different time periods. The effect of maternal ancestry on infection level was evident; hybrids exhibiting common bream mtDNA were more strongly parasitized by digeneans and crustaceans than hybrids exhibiting roach mtDNA. Hybrids harboured a majority of the specific parasites of both parental species; however, the level of infection of common bream-specific parasites (especially monogeneans) in hybrids was low. Such an asymmetrical distribution of parental species-specific parasites in hybrids may suggest the limited inheritance of protective immunological mechanisms from one parental species and reveal stronger coadaptation between common bream and its specific parasites.
Keywords: Fish Diseases; Cyprinid fish; Genetic Predisposition to Disease; Interspecific hybrids; Adaptation, Physiological; Sea Bream; Parasite communities; fyziologická adaptace; Cyprinidae; hostitelská specificita; Host Specificity; Animals; parazitární nemoci u zvířat; zvířata; nemoci ryb; Parasitic Diseases, Animal; Hybridization, Genetic; hybridizace genetická; Maternal ancestry; Host specificity; genetická predispozice k nemoci; mořan zlatý